Penatalaksanaan Fisioterapi pada Kasus Plantar Fasciitis Bilateral dengan Modalitas Phonophoresis dan Foot Core Strengthening - Fadhilah Racheal Vidyan Putri Syi; Putra Hadi; Faridah Faridah (3031-8572, 2022)
Plantar fasciitis is a heel pain syndrome where there is inflammation or irritation of the plantar fascia, with small tears in the area that attaches to the heel bone that is characterized by pain in the morning when you get up to stand and when you first step. Pain will recur in the afternoon or before bedtime when after doing various excessive and continuous activities. This study aims to determine the management of physiotherapy in bilateral plantar fasciitis using phonophoresis and foot core strengthening modalities in reducing pain, increasing muscle strength, and increasing functional activity. The method used is a case study method with one respondent, conducted in July 2022 with therapy four times a week. The measuring instrument used in this case study is pain with VAS, muscle strength with MMT, and functional activity with the jette scale. The results after being given four treatments of therapy, it was found that there was a reduction in pain, no increase in muscle strength, and an increase in functional activity. The conclusion of this study is that phonophoresis and foot core strengthening can reduce pain, there is no increase in muscle strength and increase in functional activity.